2015
DOI: 10.1016/j.hlc.2015.06.272
|View full text |Cite
|
Sign up to set email alerts
|

Circuit impedance could be a crucial factor influencing radiofrequency efficacy and safety. A myocardial phantom study

Abstract: S225 cant bradycardia. Examination of traces has not revealed any recurrence of heart block. Conclusion: This was an unusual case of severe transient conduction disturbance with unknown cause. Careful consideration is needed before undertaking long-term device therapy in young patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 0 publications
2
2
0
Order By: Relevance
“…Consistent with the results of previous studies, 6,7,10,11 using various statical approaches, our ex vivo experiments progressively demonstrated that at similar AI values, baseline impedance exhibited a strong negative linear correlation with lesion dimensions, particularly lesion depth. Namely, ablation at lower baseline impedance resulted in larger lesion dimensions created by the same level of AI, which could be explained by a simple linear formula, albeit necessitating further investigation under other conditions.…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…Consistent with the results of previous studies, 6,7,10,11 using various statical approaches, our ex vivo experiments progressively demonstrated that at similar AI values, baseline impedance exhibited a strong negative linear correlation with lesion dimensions, particularly lesion depth. Namely, ablation at lower baseline impedance resulted in larger lesion dimensions created by the same level of AI, which could be explained by a simple linear formula, albeit necessitating further investigation under other conditions.…”
Section: Discussionsupporting
confidence: 91%
“…Consistent with the results of previous studies, 6,7,10,11 also reported a similar conclusion that impedance could influence ablation lesions, however, the impedance values in their experiment were distinctly lower than ours, which were more consistent with the real clinical practice. In addition, our study has revealed a threshold impedance-150 Ω, over which the predictive accuracy of AI seems to be compromised, given that the AI formula prospectively predicted lesion depth with high accuracy of ±1 mm in the context of AI-guided ablation.…”
Section: Impact Of Baseline Impedance On Ablation Lesionssupporting
confidence: 92%
See 2 more Smart Citations